KOLAJAR 12 (KOMUNITAS GURU PEMBELAJAR 12) SEBAGAI SARANA MENINGKATKAN KOMPETENSI GURU DI SMAN 12 BANDUNG - Ananda Cipta Pamungkas; Enok Nurjanah (CAPITALIS: JOURNAL OF SOCIAL SCIENCES, 2025)
The independent curriculum gives teachers at SMAN 12 Bandung the freedom to create quality learning that suits students' needs and learning environment. The paradigm changes aimed at include strengthening the independence of teachers as holders of control in the learning process, releasing control over standards that are too binding and demand a homogeneous learning process in all educational units in Indonesia, and strengthening the rights and abilities of students to determine their learning process through determining learning goals, reflecting on his abilities, and taking steps proactively and responsibly for his own success. Based on the results of the review and observation of the implementation of the independent or IKM curriculum at SMAN 12 Bandung, there are still several IKM instruments that need to be strengthened, including those related to the preparation of ATP and Teaching Modules, P5 activities (Strengthening Pancasila Student Profile Project), and Differentiated learning. This research is a qualitative descriptive research that is reflective exploratory in nature. The subjects of this research were teachers at SMAN 12 Bandung in various subjects. The data collection mechanism is by conducting FGDs with all teachers at SMAN 12 Bandung. Meanwhile, the steps to be implemented in the data analysis method include (1) Situation, (2) Task, (3) Action, (4) Result. The Learning Teacher Community or Kolajar 12 is the method desired by teachers as a means of increasing the competence of teachers at SMAN 12 Bandung.